Проєкти зеленого будівництва Кракова: пошук кращих практик для відбудови України - Фесенко, Т. Г.; Фесенко, Г. Г. (КНУБА, 2023)
Проєкти зеленого будівництва Кракова: пошук кращих практик для відбудови України
Keywords: Стратегія розвитку